Neural Burst Firing and Its Roles in Mental and Neurological Disorders - Shao, Jie; Liu, Yunhui; Gao, Dashuang; Tu, Jie; Yang, Fan (Frontiers in Cellular Neuroscience, 2021)
Neural firing patterns are critical for specific information coding and transmission, and abnormal firing is implicated in a series of neural pathologies. Recent studies have indicated that enhanced burst firing mediated by T-type voltage-gated calcium channels (T-VGCCs) in specific neuronal subtypes is involved in several mental or neurological disorders such as depression and epilepsy, while suppression of T-VGCCs relieve related symptoms. Burst firing consists of groups of relatively high-frequency spikes separated by quiescence. Neurons in a variety of brain areas, including the thalamus, hypothalamus, cortex, and hippocampus, display burst firing, but the ionic mechanisms that generating burst firing and the related physiological functions vary among regions. In this review, we summarize recent findings on the mechanisms underlying burst firing in various brain areas, as well as the roles of burst firing in several mental and neurological disorders. We also discuss the ion channels and receptors that may regulate burst firing directly or indirectly, with these molecules highlighted as potential intervention targets for the treatment of mental and neurological disorders.